Treatment Project Design for Weakly Saline Water Bodies in Desert Parks and Practice - FENG Yu; ZHANG Wenlei; XU Yufeng; ZHANG Huajun (Renmin Zhujiang)
The eutrophication control of a saline park water body in the Inner Mongolia Plateau is conducted by constructing a complete aquatic ecosystem.Acid-alkali adjustment of this water body is carried out to build aquatic plant and animal communities in the lake body,and functional bacterial agents are also supplemented to build and restore microbial communities.Moreover,the stable development of the ecosystem is guaranteed by on-site maintenance measures.The project effect shows that the aquatic ecosystem remains stable after its successful construction,with a clear water body that offers a favorable pollutant removal effect and main water quality indexes significantly better than those before treatment.Specifically,the pH of the water body decreases from 9.09 to 8.75,and the turbidity is lowered from 20.5 NTU to 4.0 NTU.Regarding transparency,it reaches more than 1.5 m at the deepest part of the water body,or even a clear bottom is achieved.The total phosphorus concentration decreases from 0.19 mg/L to 0.03 mg/L,and the CODCr concentration is reduced from 109.5 mg/L to 17.0 mg/L.In addition,aquatic animal biomass and the number of species of aquatic animals increase significantly.The above results indicate that the water quality improvement target is achieved.The aquatic ecosystem after treatment with maintenance measures can resist external disturbance to a certain extent,and the implementation of this project can provide a reference for the treatment of saline lakes in plateau areas.